Design, optimization and evaluation of glipizide solid self-nanoemulsifying drug delivery for enhanced solubility and dissolution - Dash, Rajendra Narayan (Saudi Pharm J, 2015)
A solid self-nanoemulsifying drug-delivery system (solid SNEDDS) has been explored to improve the solubility and dissolution profile of glipizide. SNEDDS preconcentrate was systematically optimized using a circumscribed central composite design by varying Captex 355 (Oil), Solutol HS15 (Surfactant) and Imwitor 988 (Co-surfactant). The optimized SNEDDS preconcentrate consisted of Captex 355 (30% w/w), Solutol HS15 (45% w/w) and Imwitor 988 (25% w/w). The saturation solubility (SS) of glipizide in optimized SNEDDS preconcentrate was found to be 45.12 ± 1.36 mg/ml, indicating an improvement (1367 times) of glipizide solubility as compared to its aqueous solubility (0.033 ± 0.0021 mg/ml). At 90% SS, glipizide was loaded to the optimized SNEDDS. In-vitro dilution of liquid SNEDDS resulted in a nanoemulsion with a mean droplet size of 29.4 nm. TEM studies of diluted liquid SNEDDS confirmed the uniform shape and size of the globules. The liquid SNEDDS was adsorbed onto calcium carbonate and talc to form solid SNEDDS. PXRD, DSC, and SEM results indicated that, the presence of glipizide as an amorphous and as a molecular dispersion state within solid SNEDDS. Glipizide dissolution improved significantly (p < 0.001) from the solid SNEDDS (∼100% in 15 min) as compared to the pure drug (18.37%) and commercial product (65.82) respectively.